A semi‐automatic solid phase extraction system based on MIL‐101(Cr) foam‐filled syringe for detection of triazines in vegetable oils. Issue 6 (26th January 2021) - Jiang, Yanxiao; Li, Xu; Piao, Huilan; Qin, Zucheng; Li, Jingkang; Sun, Ying; Wang, Xinghua; Ma, Pinyi; Song, Daqian
Abstract: In this study, several metal‐organic framework‐melamine foam columns were first developed and used as a laboratory‐made semi‐automatic solid phase extraction packed in syringe adsorber for the extraction of six triazine herbicides from vegetable oil samples coupled to high‐performance liquid chromatography‐tandem mass spectrometry. The metal‐organic framework‐foam columns were prepared using a simple approach by embedding the solid particles in melamine foam using polyvinylidene difluoride physical encapsulation. The method was applicable to a wide variety of metal‐organic framework materials, and the incorporated materials retained their unique properties. Key factors that affect the extraction efficiency, including the MIL‐101(Cr) amount, sample flow rate, type and volume of the eluting solvent, and flow rate of eluting solvent, were investigated. Under optimum conditions, the proposed method exhibited low limits of detection (0.017–0.096 ng/mL, S/N = 3) for six triazines. The relative standard deviations calculated for all herbicides ranged from 0.2 to 14.9%. This study demonstrated that the MIL‐101(Cr)‐foam column can be used as a high‐quality adsorption material for the detection of triazines in vegetable oils.